Monitoring residues of pesticides in food in Brazil: A multiscale analysis of the main contaminants, dietary cancer risk estimative and mechanisms associated - Bitencourt de Morais Valentim, Juliana Maria; Fagundes, Tatiane Renata; Okamoto Ferreira, Mariane; Lonardoni Micheletti, Pâmela; Broto Oliveira, Geise Ellen; Cremer Souza, Milena; Geovana Leite Vacario, Beatriz; Silva, Janaína Carla da; Scandolara, Thalita Basso; Gaboardi, Shaiane Carla; Zanetti Pessoa Candiotto, Luciano; Mara Serpeloni, Juliana; et al. (Frontiers in Public Health, 2023)
Introduction Pesticides pose a risk for cancer development and progression. People are continuously exposed to such substances by several routes, including daily intake of contaminated food and water, especially in countries that are highly pesticide consumers and have very permissive legislation about pesticide contamination as Brazil. This work investigated the relationship among pesticides, food contamination, and dietary cancer risk. Methods Analyzed two social reports from the Brazilian Government: the Program for Analysis of Residues of Pesticides in Food (PARA) and The National Program for Control of Waste and Contaminants (PNCRC). Results and discussion First, we characterized the main pesticide residues detected over the maximum limits allowed by legislation or those prohibited for use in food samples analyzed across the country. Based on this list, we estimated the dietary cancer risks for some of the selected pesticides. Finally, we searched for data about dietary cancer risks and carcinogenic mechanisms of each pesticide. We also provided a critical analysis concerning the pesticide scenario in Brazil, aiming to discuss the food contamination levels observed from a geographical, political, and public health perspective. Exposures to pesticides in Brazil violate a range of human rights when food and water for human consumption are contaminated.